An empirical model of the decision to switch between electricity price contracts. (2nd January 2019) - Lanot, Gauthier; Vesterberg, Mattias
ABSTRACT: In this paper, we explore how sensitive the timing of switches between electricity contracts is to current and past prices. We present a model for time series of individual binary decisions which depends on the history of past and present prices. The model is based on the Bayesian learning procedure which is at the core of sequential decision-making. Given a-priori distributions of the information conditional on the state of the world, we show that the model captures dependence on past prices in a straightforward fashion. We estimate by maximum likelihood the parameters of the model on a sample of Swedish households who decide over time between competing electricity price contracts. The estimated parameters suggest that households do respond to prices by switching between contracts and that the response to price can be sizeable for alternative price processes. Importantly, the model structure implies that in general, the response to a price change will not be immediate but delayed.